STUDI EKSPERIMEN PENGARUH COACHING QUALITY TERHADAP KOMITMEN ORGANISASI PADA AUDITOR DI SURABAYA - Wardani, Rr. Puruwita; Wibowo, Vivian Angelina Soegiharto; Sabatini, Ester; Hartanto, Susanna (Prodi Akuntansi FEB UNITOMO, 2024)
This research examines organizational commitment in the form of the auditor's intention or desire to move or leave KAP. Auditor commitment can be formed through coaching quality. The coaching quality influences the auditor's commitment to carrying out audits with full responsibility. This research aims to analyze the relationship between coaching quality and organizational commitment. Participants in this research were junior and senior auditors, supervisors, and managers from one of the foreign-affiliated KAPs in Surabaya. Based on learning-member exchange theory, the quality of exchange relationships developed by leaders can have implications for auditor performance so high-coaching quality will minimize the auditor's intention to move or leave the KAP. The research results prove that the intention or desire to leave for auditors who receive high-quality coaching is lower than the intention or desire to leave for auditors who receive low-quality coaching. Coaching quality needs to be improved so that the auditors being coached have critical thinking. Keywords: organizational commitment, coaching quality, auditor, learning-member exchange theory